2008
DOI: 10.1080/15563650701549403
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma paraquat level and outcome of paraquat poisoning in 375 paraquat poisoning patients

Abstract: Our data showed that plasma paraquat concentration is good predictor of survivors but is not good predictor of non-survivors in the low plasma paraquat level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 18 publications
2
72
1
Order By: Relevance
“…In fact, case studies by Lee et al [4] suggest that lung damage may not be irreversible if treated early. Thus, identification of lesions in the lungs and their severity may be crucial to improve patients' outcomes, especially since the number of lung lesions has been associated with greater mortality rates in these patients [20]. Notably, the current study confirms the association between the number of lesions and mortality, although further studies will be required to identify whether earlier treatment or alternative treatment modalities, such as anti-oxidant or immunosuppressive treatments, could be used to improve the outcome.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, case studies by Lee et al [4] suggest that lung damage may not be irreversible if treated early. Thus, identification of lesions in the lungs and their severity may be crucial to improve patients' outcomes, especially since the number of lung lesions has been associated with greater mortality rates in these patients [20]. Notably, the current study confirms the association between the number of lesions and mortality, although further studies will be required to identify whether earlier treatment or alternative treatment modalities, such as anti-oxidant or immunosuppressive treatments, could be used to improve the outcome.…”
Section: Discussionsupporting
confidence: 68%
“…This result is similar to that of our previous clinical trial [10] demonstrating that repeated pulse therapy results in better survival than conventional therapy in patients with severe PQ poisoning. Moreover, a previous study [18] including 375 patients with PQ poisoning demonstrated that the upper threshold of plasma PQ levels is 2.64 mg/l at 3 h after PQ ingestion. All patients with a plasma PQ level above 3.44 mg/l died.…”
Section: Discussionmentioning
confidence: 99%
“…Death generally occurs 24-72 h after ingestion, with causes including acute respiratory failure, acute renal failure, acute hepatic failure and multiple organ dysfunction syndrome. 1,18 The present study found that, compared with HP alone, HP þ CVVH increases survival time but does not improve the mortality rate of patients with acute paraquat poisoning.…”
Section: Discussionmentioning
confidence: 81%
“…1 Attempts to modify the toxicity of paraquat have proven ineffective, and the clinical outcome of poisoning is therefore determined by degree of exposure. [2][3][4][5][6] The primary mechanism of exposure is ingestion, after which paraquat accumulates primarily in the lungs, resulting in acute pulmonary distress.…”
Section: Introductionmentioning
confidence: 99%